(3eaGgje MOjKI aj GdQbGHI GdeGdjI hGdOGNdjIaj GdbWGY GdYGe hGdNGU (B/s - (3GdNWjH, NGdO QGZHs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2009)
(3eGgjI GdQbGHI GdOGNdjI, UdGMjGJ GdJObjb, fXGe GdQbGHI Ydi GdeGd GdYGe, GdQbGHI GdeGdjI aj GdfXGe GdGSdGej, GdGSJKeGQ aj GdJWhjQs
(3HHdjhZQGajG(B: (3U(B.253-254s
Keywords: (3GdQbGHI GdeGdjIs; (3GdbWGY GdNGUs; (3GdbWGY GdYGes